Programming PIC microcontrollers using PICBASIC - Hellebuyck, Chuck (Embedded technology series., 2003)
This comprehensive tutorial assumes no prior experience with PICBASIC. It opens with an introduction to such basic concepts as variables, statements, operators, and structures. This is followed by discussion of the two most commonly used PICBASIC compilers. The author then discusses programming the most common version of the PIC microcontroller, the 15F84. The remainder of the book examines several real-world examples of programming PICs with PICBASIC. In keeping with the integrated nature of embedded technology, both hardware and software are discussed in these examples; circuit details are given so that readers may replicate the designs for themselves or use them as the starting points for their development efforts. *Offers a complete introduction to programming the world's most commonly used microcontroller, the Microchip PIC, with the powerful but easy to use PICBASIC language *Gives numerous design examples and projects to illustrate important concepts *Accompanying CD contains the source files and executables discussed in the book as well as an electronic version of the book.